Pustular psoriasis of pregnancy (Impetigo herpetiformis) - case report - Rogerio Nabor Kondo; Fernanda Mendes Araújo; Allamanda Moura Pereira; Vivian Cristina Holanda Lopes; Ligia Márcia Mario Martins (Sociedade Brasileira de Dermatologia, 2013)
Impetigo herpetiformis is a rare dermatosis of pregnancy with typical onset during the last trimester of pregnancy and rapid resolution in the postpartum period. Clinically and histologically, it is consistent with pustular psoriasis. This similarity has led some authors to name the disease "the pustular psoriasis of pregnancy". We report the case of a patient who developed impetigo herpetiformis in two sucessive pregnancies.